Laser-driven strong magnetostatic fields with applications to charged beam transport and magnetized high energy-density physics - Rose,SJ; Santos,JJ; Bailly-Grandvaux,M; Ehret,M; Arefiev,AF; Batani,D; Beg,FN; Calisti,A; Ferri,S; Florido,R; Forestier-Colleoni,P; Fujioka,S; et al. (Physics of Plasmas, 2018)
Powerful laser-plasma processes are explored to generate discharge currents of a few 100 kA in coil targets,yielding magnetostatic fields (B-fields) in excess of 0.5 kT. The quasi-static currents are provided from hotelectron ejection from the laser-irradiated surface. According to our model, which describes the evolution ofthe discharge current, the major control parameter is the laser irradianceIlasλ2las. The space-time evolutionof the B-fields is experimentally characterized by high-frequency bandwidth B-dot probes and by proton-deflectometry measurements. The magnetic pulses, of ns-scale, are long enough to magnetize secondary targetsthrough resistive diffusion. We applied it in experiments of laser-generated relativistic electron transportthrough solid dielectric targets, yielding an unprecedented 5-fold enhancement of the energy-density flux at60μm depth, compared to unmagnetized transport conditions. These studies pave the ground for magnetizedhigh-energy density physics investigations, related to laser-generated secondary sources of radiation and/orhigh-energy particles and their transport, to high-gain fusion energy schemes and to laboratory astrophysics.